Mineralogy and environmental stability of metallurgical slags from the Euronickel smelter, Vozarci, North Macedonia - Đorđević, Tamara; Tasev, Goran; Aicher, Claudia; Potysz, Anna; Nagl, Peter; Lengauer, Christian L.; Pędziwiatr, Artur; Serafimovski, Todor; Boev, Ivan; Boev, Blažo (Applied geochemistry, 2024)
The laterite Ni-smelting operations at Vozarci, Republic North Macedonia have produced large amounts of smelting wastes dumped in the close vicinity of the smelter. We examined phase composition and chemistry of the various types of slags (electric furnace slags, converter slag, magnetic slag) with the special focus on the phases containing potentially toxic elements in terms of their mineralogy, chemical composition, and responses to weathering. Electric furnace slags contain between 35 and 47 wt.% SiO2, 21–40 wt.% Fe2O3, and 13–23 wt.% MgO; converter and magnetic slags are Fe-rich (76–77 wt.% of Fe2O3) with significant amounts of Ca (7.6–8.4 wt.% CaO) and S-portion (2–2.5 wt.% SO3). All slags contain substantial amounts of the potentially toxic elements: Co (20–87 ppm), Cr (9600–17400 ppm), Ni (170–730 ppm), and Zn (150–380 ppm). Further mineralogical analyses showed that the slags consist of silicate glass, synthetic equivalents of olivines, orthopyroxenes, clinopyroxenes, and subordinate spinel-group phases, sulfides, and intermetallic compounds. Some of the slags had been subject to weathering since their dumping in 1982. The weathering results in the release of metals from primary slag phases, particularly from glass, and the partial immobilization of these metals in secondary soluble and insoluble minerals in the slag heaps (hydroxy-iron oxides, gypsum, anhydrite, syngenite, aphthitalite). The majority of slag samples exhibited increased leaching under conditions of lower pH (2.9) compared to higher pH (4.9). The contrast between leaching treatments was particularly evident for nickel (Ni), with leaching at a low pH of 2.9 reaching up to 135 times higher (MS) than at pH 4.9. At lower pH conditions, other contaminants of interest were leached out at a rate 4 to 76 times faster compared to the leaching achieved at pH 4.9, because they are the major source of potentially toxic elements. [Display omitted] •Phase composition of electric furnace slags and converter slags are distinct.•Slags contain on average 10467 ppm Cr, 1050 ppm Ni, 233 ppm Zn.•Major hosting phase for Cr are spinel-group oxides.•Major hosting phase for Ni are sulfides and intermetallic compounds.•Leaching tests demonstrated low risk of contamination referred to TCLP norm.